Enhanced visible light photocatalysis through fast crystallization of zinc oxide nanorods - Baruah, Sunandan; Mahmood, Mohammad Abbas; Myint, Myo Tay Zar; Bora, Tanujjal; Dutta, Joydeep (Beilstein Journal of Nanotechnology, 2010)
Hydrothermally grown ZnO nanorods have inherent crystalline defects primarily due to oxygen vacancies that enhance optical absorption in the visible spectrum, opening up possibilities for visible light photocatalysis. Comparison of photocatalytic activity of ZnO nanorods and nanoparticle films on a test contaminant methylene blue with visible light irradiation at 72 kilolux (klx) showed that ZnO nanorods are 12–24% more active than ZnO nanoparticulate films. This can be directly attributed to the increased effective surface area for adsorption of target contaminant molecules. Defects, in the form of interstitials and vacancies, were intentionally created by faster growth of the nanorods by microwave activation. Visible light photocatalytic activity was observed to improve by ≈8% attributed to the availability of more electron deficient sites on the nanorod surfaces. Engineered defect creation in nanostructured photocatalysts could be an attractive solution for visible light photocatalysis.
Keywords: defects; nanoparticle; nanorod; photocatalysis; pollutant; ZnO